Cannabinoid effects on responses to quantitative sensory testing among individuals with and without clinical pain: a systematic review. Issue 2 (February 2020) - Mun, Chung Jung; Letzen, Janelle E.; Peters, Erica N.; Campbell, Claudia M.; Vandrey, Ryan; Gajewski-Nemes, Julia; DiRenzo, Dana; Caufield-Noll, Christine; Finan, Patrick H.
Abstract : Abstract: There has been an explosion of interest in the utility of cannabinoids as potential analgesics. This systematic review critically synthesizes the evidence for cannabinoid analgesic effects on quantitative sensory testing outcomes in both healthy adults and patients with chronic noncancer pain. Our systematic review protocol is preregistered on PROSPERO (CRD42018117367). An electronic search was made in PsycINFO, Cochrane, Google Scholar, Embase, and Pubmed of all literature published until August 2018. Of the 1217 studies found from the search, a total 39 placebo-controlled studies that met the eligibility criteria were synthesized for this study. Because of substantial heterogeneity of study designs, populations, cannabinoid compounds, and quantitative sensory testing outcomes, meta-analysis was not conducted. More consistent evidence of cannabinoid analgesia was observed for inhaled cannabis than synthetic cannabinoids. Analgesic effects were most commonly observed in tests of cold pain sensitivity, and hyperalgesic effects were most commonly observed in tests of electrical stimulation. Patterns of findings from studies with healthy subjects did not substantively differ from those with chronic noncancer pain. However, these observations are qualified by the high degree of inconsistency across studies and methodological heterogeneity. We offer recommendations for future studies to improve study rigor and reproducibility.